Analisa Dan Implementasi Algoritma Enkripsi Simetris Data Encryption Standard (DES) Pada Raspberry Pi - Erick Fernando; Dina Fitria Murad; Hetty Rohayani; Fachruddin Fachruddin; Pandapotan Siagian (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2019)
The purpose of this article is to present DES encryption on the Raspberry Pi mini pc. This implementation also aims to illustrate that the DES algorithm can be applied with small resources. This research was carried out by an experimental approach, which carried out the implementation process in mini pc hardware and xampp software. The DES algorithm is implemented web-based with PHP programming with the Apache web server using text data. The results of the study, that the DES algorithm can run well with minimum hardware, such as mini pc raspberry with a very fast time in the process, speed in the process and lots of text data from the process. So, the DES algorithm can be widely adopted for various applications from the mini Raspberry PI by producing information that is strong in security and reliability.